Perbandingan antara Arts & Crafts Movement dan Democratic Design dalam Menghadapi Laju Perubahan Revolusi Industri. - Rahadi, Panji Firman (Visualita Jurnal Online Desain Komunikasi Visual, 2020)
The industrial revolution that occurred in Europe until the 20th century is considered as a human achievement that changed the world. The pace of change brought by the Industrial Revolution starting from the first wave (1.0) to the fourth (4.0) led to various responses from various sectors, including from the art world. The Arts & Crafts Movement and the Democratic Design are examples of these forms of response. The relationship between those movements in art history is very afar. The two of them are separated for more over than two centuries. Both are movements that are based on a new thought and are changes in movements that affect changes in the future. This study was conducted to find the similarities of the two movements, to see the thoughts of the two and their impact on the development of design in the world up to this century. The study was conducted based on a literature study.